Thoracoscopic left ventricular lead implantation - Pojar, Marek; Vojáček, Jan; Tauchman, Miloslav; Pařízek, Petr; Havlíček, Aleš; Bělohlávek, Jan; Haman, Luděk (Acta cardiologica, 2011)
OBJECTIVE: Cardiac resynchronization therapy is a therapeutic option in patients with chronic heart failure. Epicardial lead implantation for biventricular pacing is usually the method of second choice after failed coronary sinus cannulation. The present study describes an initial experience with minimally invasive surgical lead implantation using thoracoscopy. METHODS: Since August 2008, a total of 17 patients (mean age 69.6 + 11.1 years) with congestive heart failure, NYHA functional class 3.1 +/- 0.4, and depressed ejection function (24.8% +/- 5.7%) were referred for surgery because of failed left ventricular lead implantation through the coronary sinus. Under single-lung ventilation and video-assisted thoracoscopy, epimyocardial steroid-eluting screw-in leads were implanted on the left ventricular free wall. RESULTS: There were no in-hospital deaths or major co-morbidities. The mean skin-to-skin operating time was 115.9 +/- 32.1 min, and the post-operative average length of stay was 8.4 +/- 2.5 days. Intraoperative acute threshold capture of the left ventricular lead was 0.88 +/- 0.54 V/0.5 ms, and the value of lead impedance was 434.7 +/- 110.8 Omega. Extension to a small thoracotomy was necessary in 1 patient to stop epicardial vein bleeding. CONCLUSION: Minimally invasive left ventricular lead implantation is a safe procedure with excellent acute threshold capture.
Keywords: Female; Thoracic Surgery, Video-Assisted; Electrodes, Implanted; výsledek terapie; ženské pohlaví; Heart Failure; Cardiac Resynchronization Therapy; lidé; srdeční selhání; Treatment Outcome; Aged, 80 and over; srdeční resynchronizační terapie; hrudní chirurgie video-asistovaná; Male; Aged; implantované elektrody; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans